Nanoparticles Engineered as Artificial Antigen-Presenting Cells Induce Human CD4+ and CD8+ Tregs That Are Functional in Humanized Mice - Giang, Sophia; Horwitz, David A.; Bickerton, Sean; La Cava, Antonio (Frontiers in Immunology, 2021)
Artificial antigen-presenting cells (aAPCs) are acellular, synthetic versions of naturally occurring antigen-presenting cells (APCs) that, similar to natural APCs, promote efficient T effector cell responses in vitro. We report that aAPCs made of biodegradable poly lactic-co-glycolic acid (PLGA) nanoparticles (NPs) and encapsulating tolerogenic cytokines for a paracrine release to T cells can induce both human CD4+ and CD8+ T cells to become FoxP3+ T regulatory cells (Tregs). The aAPC NP-expanded human Tregs are functional in vitro and can modulate systemic autoimmunity in vivo in humanized NSG mice. These findings establish a proof-of-concept to use PLGA NPs as aAPCs for the induction of human Tregs in vitro and in vivo, highlighting the immunotherapeutic potential of this approach in human systemic autoimmune disease.